Impact of a Weekly Multidisciplinary Tumor Board Conference on the Management of Women With Gynecologic Malignancies. Issue 8 (1st October 2010) - Greer, Heather O.; Frederick, Peter J.; Falls, Nicole M.; Tapley, Emily B.; Samples, Karen L.; Kimball, Kristopher J.; Kendrick, James E.; Conner, Michael G.; Novak, Lea; Straughn, J. Michael
Abstract : Background: The objective of this study was to evaluate the impact of a weekly tumor board conference on the management of patients with gynecologic malignancies. Methods: The medical records of consecutive patients referred to a multidisciplinary gynecologic oncology tumor board were reviewed. Patient demographics were abstracted from medical records and tumor board minutes. An evaluation was made whether the pathological or radiological findings were changed by the tumor board consultants. If a discrepancy existed, it was determined whether the change impacted clinical management. Results: From January 2004 to December 2006, 741 patients presented at the tumor board were evaluable. Seventy-one percent of the patients were presented for pathology review and 29% for radiology review. The most common diagnoses were ovarian cancer (29%), endometrial cancer (26%), and cervical cancer (12%). Of the 526 pathology reviews, 27% had a change in diagnosis; this discrepancy altered clinical management 74% of the time (20% of all reviews). Of the 215 radiology presentations, 89% were reviewed to confirm recurrent or persistent disease; malignant disease was confirmed 74% of the time. Review of imaging studies resulted in a new diagnosis or upstaging 10% of the time. Conclusions: A multidisciplinary tumor board allows a wide range of gynecologic diagnoses and clinical scenarios to be discussed. Careful review of pathology results in a change in the clinical management of 20% of patients presented at the tumor board. The majority of radiology reviews are presented to confirm persistent or recurrent cancer before recommending further therapy.